Purification and Characterization of a Flavone-7-O-Glucoside Specific Glucosidase from Ligulate Florets of Chamomilla recutita - Maier, Reinhard; Carle, Reinhold; Kreis, Wolfgang; Reinhard, Ernst (Planta Medica, 1993)
Flavone content and glucosidase activity were analyzed in various species of the genera Chamomilla, Matricaria, and Anthemis, especially during the development of the chamomile flower heads. The accumulation profile of flavonoids and the increase in enzyme activity were similar during ontogenesis. The accumulation of apigenin derivatives in closely related species was always linked to the occurrence of a catabolic β-glucosidase in the respective plant organ. The flavone-glucoside-cleaving β-glucosidase (FGG) from the ligulate florets of chamomile was purified to electrophoretic homogeneity by the following procedure: ammonium sulphate fractionation, anion exchange on Mono Q, hydrophobic interaction chromatography on Bio-Gel TSK Phenyl-5-PW, and gel filtration on Superose 12. The M(r) of the native enzyme was determined by gel filtration (500 kDa) and native PAGE (334 kDa). Only one subunit with an M(r) of 60 kDa could be detected after SDS-PAGE. The isoelectric point as determined by chromatofocussing on Mono P was at pH 4.6. During the purification procedure only one glucosidase activity appeared. A partially purified enzyme was used for characterization. The temperature optimum was at 37°C and the pH-optimum 5.6. Energy of activation was 32.9 kJ/mol. The determination of the kinetic constants with various aryl glycosides proved a high affinity of the FGG towards flavone 7-O-glucosides. α-Glycosides and disaccharides were not hydrolyzed. Transglucosylation to an acceptor other than water was observed. Reagents interacting with sulfhydryl-groups strongly inhibited the enzyme.
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.purifi
Keywords: chamomile flower heads; Chamomilla recutita; flavone 7-O-glucosides; glucosidase